Synergistic effect of Promoter addition and Nickel Loading for Catalysed Dry Reforming of Methane - Suppiah, Durga Devi (Malaysian Catalysis-An International Journal, 2022)
This paper investigates the synergistic influence of both catalyst active sites Lanthanum promoter and Nickel loading on supported Ni catalysts for Dry Reforming of Methane (DRM) reaction. Alumina-supported nanosized Ni-based catalysts were synthesized using the impregnation method with varying percentages of Lanthanum promoter. Structural analysis via XRD, SEM and PSD show Nickel and lanthanum were homogeneously dispersed on Al2O3 supported catalyst with a range of 40-90 nm were obtained. Lanthanum addition favours equilibrated reaction equivalent to DRM mechanism. Increasing the La percentage and temperature however shifts the equilibrium to a higher conversion of CH4 (72%) hence higher H2 selectivity (70%).